Medium-sized towns in the knowledge economy: towards a systematic classification - Wagner, Madeleine; Growe, Anna (Sustainability, 2023)
Medium-sized towns represent important anchor points with regard to services of general interest that are also places to live and work. The increasing number of employees in the service and knowledge economy and the shift in working conditions towards more flexible and mobile working models have impacted the importance of working locations outside the metropolises. This study classifies all medium-sized German towns with a focus on the knowledge economy to analyze the role of this city type for different labor market indicators. First, 19 indicators are condensed into six principal components by means of principal component analysis. This is followed by a cluster and a discriminant analysis to determine five types of towns: (1) important working and education centers, (2) residential towns with a work function, (3) average medium-sized towns, (4) accessibility winners, and (5) tax winners. The results demonstrate that medium-sized towns should be regarded as a single and important urban category, especially concerning the knowledge economy. Our classification enables an initial evaluation that can be used for further evidence-based funding policy and spatial governance. By concluding with a methodological critique and discussing the results obtained, we argue for a more nuanced look at medium-sized towns from different disciplinary perspectives.
Gesehen am 15.03.2023